UJI PURI SEBAGAI GAMBARAN STATUS HIDRASI JANGKA PENDEK SELAMA JAM KULIAH PADA MAHASISWA - Herawati, Elysabet; Wijayanti, Endah Tri (Pattimura University, 2023)
The large number of activities without being balanced with sufficient consumption of drinking water can affect the hydration status of the body, namely the occurrence of dehydration. The study aims to describe the short-term hydration status of D-III Nursing Study Program students in terms of the PURI test results. The method used is the PURI test, namely the urine self-check method which is carried out in 2 tests. The research also used a survey method to support the results of the PURI test. Based on the results of the study, the short-term hydration status of D-III Nursing Study Program students based on the PURI test on the results of the 1st test showed that most of the students 15% experienced mild dehydration and 72% experienced severe dehydration. This is related to the habit of students who never bring drinking water to campus and most students do not consume enough water during the range of lecture hours until the lecture is over. The results of the 2nd PURI test showed that 76% of students had good hydration status because prior to testing students were encouraged to consume sufficient amounts of water. The results of the study show that students awareness of meeting body fluids to maintain body fluid homeostasis needs to be increased.